KEARIFAN LOKAL DALAM REKONSTRUKSI PERUMAHAN PASCA BENCANA GEMPA DAN TSUNAMI - INDRAMANIK, IDA BAGUS GEDE; SUDARSANA, DEWA KETUT; ASTANA, I NYOMAN YUDHA; YANA, A.A.GEDE AGUNG (Universitas Mahasaraswati K. Mataram, 2024)
Natural disasters, such as earthquakes and tsunamis, leave a detrimental impact on people, disrupt lives and cause extensive damage. The results of post-disaster reconstruction must be better than before so that they are more resilient in facing future disasters. However, this is not easy, especially reconstruction in the housing sector due to the lack of attention to the local wisdom of the disaster victims. This study aims to identify elements of local wisdom that contribute to the success of housing reconstruction efforts after the earthquake and tsunami. This research is a literature review where the literature is collected from previous studies originating from reputable international journals which are then sorted until finally 35 articles are reviewed which are further studied. From various previous studies, it can be concluded that the types of local wisdom that need to be considered in housing reconstruction after the earthquake and tsunami disaster can be seen from the dimensions of technology and systems, religious rituals/activities, local knowledge, education and community participation. Local wisdom that must be considered is knowledge about nature and the local environment, local community customs, culture, geographical and climatic conditions, available local construction materials, traditional ways of building houses, and community participation in the reconstruction of the housing.